Surgical Management of Enchondromas of the Hand: A 12-Year Experience - Redgrave, Natalie; Nikkhah, Dariush; Kang, Norbert; Toft, Neil (Journal of Hand and Microsurgery, 2021)
Objective Enchondromas are benign tumours of hyaline cartilage most frequently arising in the bones of the hand and the optimum surgical management strategy for these is debated. We present an audit of the surgical management of 57 enchondromas referred to our tertiary hand surgery department over a period of 12 years (2008–2020) and describe our surgical technique for this procedure as well as a comparison with other studies in the literature.Materials and Methods Retrospective audit of our practice. Data were extracted from our institutional operative database to identify all patients undergoing surgical management of enchondromas during the time period. The individual electronic patient records were then evaluated to extract demographics and outcome data.Results Our results demonstrate excellent clearance of enchondroma (74% Tordai group 1 radiological resolution) with very low complication rates and no recurrence. Our results also emphasize the importance of surgical management of enchondromas to allow diagnosis of rare chondrosarcoma (3.5% in this study).Conclusion A larger randomized controlled trial is still required to adequately determine the differences between the surgical options available and determine the best possible surgical approach to these cases. Level of evidence is III.
Keywords: enchondroma; chondrosarcoma; bone tumor